IMF’s Surcharges as a Threat to the Right to Development - Bohoslavsky, Juan Pablo; Cantamutto, Francisco; Clérico, Laura (Development, 2022)
This article focuses on the implications of the IMF’s surcharges policies, jointly with its de facto preferred creditor status, on the right to sustainable development of sovereign borrowers. The article argues that, while surcharges are not effective in limiting access to IMF credit, they inequitably distribute the IMF’s operating costs, are disproportionate, pro-cyclical, very costly for developing countries, and non-transparent. Furthermore, if surcharges are theoretically a way to protect the IMF from potential risks of default, the article questions the IMF’s de facto preferred creditor status, as it precisely denies the possibility of granting debt relief in case of insolvency, ultimately affecting the right to development of —mainly— middle-income borrowing countries.
CRIS-Team Scopus Importer:2022-09-09
Keywords: Developing countries; Global Finance; Human Rights; Multilateral Loan Conditions; Preferred Creditor Status